Recent Advances on Mycorrhizal Fungi - Pagano, Marcela C. (Fungal Biology, 2016)
Recent Advances on Mycorrhizal Fungi integrates work done by pre-eminent scientists, academics, and researchers dedicated to the study of mycorrhizas in laboratories around the world. The main aim of this book is to compile the information related to mycorrhizas advancement and their applications. First, an overview of the recent advances in mycorrhizal fungi is fully examined. Then, researchers from different countries address issues related to semiarid, xeric, and agro-ecosystems. A greater understanding of the ecology of this type of fungi will underpin efforts to provide new strategies for agriculture production systems and environmental solutions. Finally, relevant topics such as plant stress and ecological succession with regard to mycorrhizal symbioses are discussed. This book will be useful to those who work with mycorrhizas and important for academic and research teams, as well as to teachers, students, professionals and farmers. This information will be a key foundation to decision-makers worldwide and also for conservationists and ecologists.